Asterix. The mansions of the gods [videorecording (DVD)]. - Astier, Alexandre, 1975-; Goscinny, 1926-1977 (Kids Viva Pictures Distribution, LLC, 2025)
Asterix and his best friend Obelix have a peaceful life in their small village, engaging in friendly town brawls and hunting in the forest. When Julius Caesar decides that this unruly town of the Gauls must be converted to a modern Roman city, he constructs luxury apartments next to the village. Realizing this is the first step in a plot to destroy their town, Asterix and Obelix must uncover Caesar's nefarious plan before it's too late and their town is lost forever.